Predicting the Distribution of Indicator Taxa of Vulnerable Marine Ecosystems in the Arctic and Sub-arctic Waters of the Nordic Seas - Burgos, Julian M.; Buhl-Mortensen, Lene; Buhl-Mortensen, Pål; Ólafsdóttir, Steinunn H.; Steingrund, Petur; Ragnarsson, Stefán Á.; Skagseth, Øystein (Frontiers in Marine Science, 2020)
In the deep waters of the Nordic Seas and adjacent areas, several benthic habitats such as cold-water coral reefs, coral gardens, and deep-sea sponge aggregations have been classified as vulnerable marine ecosystems (VMEs), due to their uniqueness, limited spatial extent, physical fragility, and slow recovery rate. In the last decade observations carried out by habitat mapping programmes in Norway, Iceland and more recently in the Faroe Islands have substantially increased knowledge on the distribution of VMEs in the Nordic Seas. Nevertheless, large areas have not been explored due to the cost and logistics of obtaining observations in the deep-sea. Species distribution models can be used to predict the distribution of VMEs and their indicator species. Here we present the predicted distribution of 44 VME indicator taxa including 20 sponges, 17 cold-water corals and 7 seapens in the Nordic Seas based on data compiled and models developed by the NovasArc project (2016-2018). Models for 44 VME indicator species were developed using a maximum entropy approach (MaxEnt) using an extensive database compiled from habitat mapping surveys, by-catch data from bottom fish surveys, and records from reports and peer reviewed publications. Modeled distributions showed good agreement with observations. Niche overlap measures were used to identify seven groups and four subgroups of VME indicator taxa that co-occur. These were consistent with the species composition of known biotopes in the study area. A VME Index that combine the predictions for all VME indicator species was computed to identify particularly valuable and vulnerable ecosystems that should be targets of further exploration and conservation efforts. Such areas were identified at shelf break and slope off Iceland, the Faroe Islands, and central Norway, and the continental shelf off southern Greenland. The predicted distribution of VMEs in arctic and sub-arctic waters allows for the evaluation of interactions with fisheries and other anthropogenic activities and provides an important input for managers.